Cycle packing1. Issue 4 (16th October 2014) - Conlon, David; Fox, Jacob; Sudakov, Benny
Abstract In the 1960s, Erdős and Gallai conjectured that the edge set of every graph on n vertices can be partitioned into O(n) cycles and edges. They observed that one can easily get an O(nlogn) upper bound by repeatedly removing the edges of the longest cycle. We make the first progress on this problem, showing that O(nloglogn) cycles and edges suffice. We also prove the Erdős‐Gallai conjecture for random graphs and for graphs with linear minimum degree. © 2014 Wiley Periodicals, Inc. Random Struct. Alg., 45, 608–626, 2014